Tanggung Jawab LPSK dalam Pelaksanaan Restitusi Korban Kekerasan Seksual oleh Pelaku yang Tidak Mampu atau Terpidana Mati - Dea Prida Oktavia; Rini Apriyani; Agustina Wati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the responsibilities of the Witness and Victim Protection Agency (LPSK) and the state in implementing restitution for victims of sexual violence, particularly when the perpetrators are unable to pay or are sentenced to death. The background of this research lies in the weak implementation of restitution, which should be a fundamental right of victims, as illustrated by the case of Herry Wirawan based on the Bandung High Court Decision Number 86/Pid.Sus/2022/PT Bdg. The research addresses two main problems: (1) how the state and LPSK ensure the victims’ rights to restitution under such circumstances, and (2) what obstacles hinder the implementation of restitution based on the decision. The study employs a normative juridical method with a statutory and case study approach. The findings show that the implementation of restitution still faces serious obstacles, such as the absence of technical mechanisms, the lack of designated executing institutions, and the lack of coordination among law enforcement agencies. LPSK plays a role in proposing and calculating restitution amounts but lacks execution authority. Moreover, the state has not yet fulfilled its role as the ultimate guarantor for victims when the perpetrator is unable to comply. In conclusion, Indonesia’s legal system needs to strengthen technical regulations, ensure inter-agency coordination, and affirm the state's role as a guarantor of restitution to achieve meaningful restorative justice for victims of sexual violence